(3acQI Yf (BOracle 11g DBAs - (3YRH, eMeO YRHs ((3GdbGgQIs (3GdOGQ GdeUQjI ddYdhes, 2008)
(3jJfGhd gPG GdcJGH GdehVhYGJ HTcd Yedi h HWQjbI LOjOI ddCNP HjO GdOGQS HCSQY hbJ eecf dJYde (BOracle 11 g Dba (3h GMJQGag ai eOI JSYI CjGes
(3GdYGde ef MhdfG (B((3GdceHjhJQ(B)s
1 11
Keywords: Computer Science; (3GdMGSHGJ GdEdcJQhfjIs